The N6‐methyladenosine (m6A) erasers alkylation repair homologue 5 (ALKBH5) and fat mass and obesity‐associated protein (FTO) are prognostic biomarkers in patients with clear cell renal carcinoma. (17th February 2020) - Strick, Alexander; von Hagen, Felix; Gundert, Larissa; Klümper, Niklas; Tolkach, Yuri; Schmidt, Doris; Kristiansen, Glen; Toma, Marieta; Ritter, Manuel; Ellinger, Jörg
Abstract : Objectives: To comprehensively investigate the role of the N 6 ‐methyladenosine (m 6 A) erasers ALKBH5 and FTO in clear cell renal cell carcinoma (ccRCC), other RCC subtypes, and oncocytoma with respect to prognostic value and biomarker potential. Patients and Methods: The collection of tissue samples was performed within the framework of the Biobank at the Centre for Integrated Oncology Cologne‐Bonn. The gene expressions of alkylation repair homologue 5 (ALKBH5) and fat mass and obesity‐associated protein (FTO) were determined using quantitative real‐time polymerase chain reaction. ALKBH5 and FTO expressions were further investigated in ccRCC, papillary RCC, chromophobe RCC, sarcomatoid RCC, oncocytoma, and benign renal tissue using tissue microarrays. Results: ALKBH5 mRNA, as well as ALKBH5 and FTO protein expressions, was significantly downregulated in ccRCC compared to normal tissue and most of the other studied tumour entities. Decreased mRNA levels of ALKBH5 and FTO correlated with a shortened overall and cancer‐specific survival following nephrectomy. Conclusions: Taken together, our present data indicate that the m 6 A‐demethylases ALKBH5 and FTO are dysregulated in ccRCC and could be used as prognostic biomarkers.